On dynamic credibility models - Ferenstein, Elżbieta (O dynamicznych modelach wiarygodności, 2020)
The Bühlamnn-Straub credibility model is extended for risk profiles varying with time. This is a special case of an evolutionary credibility model with risk parameter changing with time according to an unobserved sequence of random variables. The exact formulas of Bayes premiums are obtained for models in which the probability distributions of risk profiles switch to others at random unobserved time periods with known distributions. In particular, for exponential type class of distributions with conjugate priors, the Bayes premium is obtained recursively from a non-linear multidimensional Kalman type filter
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 133-147